2013
DOI: 10.1371/journal.pone.0060891
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Two Intra-Individual Sequence Variants in the 18S rRNA Gene in the Plant Parasitic Nematode, Rotylenchulus reniformis

Abstract: The 18S rRNA gene is fundamental to cellular and organismal protein synthesis and because of its stable persistence through generations it is also used in phylogenetic analysis among taxa. Sequence variation in this gene within a single species is rare, but it has been observed in few metazoan organisms. More frequently it has mostly been reported in the non-transcribed spacer region. Here, we have identified two sequence variants within the near full coding region of 18S rRNA gene from a single reniform nemat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 29 publications
1
13
0
Order By: Relevance
“…To the best of our knowledge, R. reniformis is the only organism among the phylum Nematoda for which this phenomenon has been described so far. These rRNA types showed substantial differences in sequences from each other: the 18S rRNA -5.5% (Nyaku et al, 2013b), the D2-D3 of 28S rRNA up to 15.6%, the ITS rRNA up to 24.5% (this study). In our study we also found two distinct ITS rRNA types for R. macrosomoides sp.…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…To the best of our knowledge, R. reniformis is the only organism among the phylum Nematoda for which this phenomenon has been described so far. These rRNA types showed substantial differences in sequences from each other: the 18S rRNA -5.5% (Nyaku et al, 2013b), the D2-D3 of 28S rRNA up to 15.6%, the ITS rRNA up to 24.5% (this study). In our study we also found two distinct ITS rRNA types for R. macrosomoides sp.…”
Section: Discussionsupporting
confidence: 48%
“…Reconstruction of secondary structure models for two types of the D2 of 28S rRNA for R. reniformis and mutation mapping showed that both models have similar conservative folding and most point mutations were compensatory, confirming that both gene rRNA types are functional. Nyaku et al (2013b) also revealed that both 18S rRNA types were expressed in nematode tissues as their sequences were present in ESTs. Fig.…”
Section: Discussionmentioning
confidence: 87%
“…The presence of indels within rRNA gene sequences may also cause problems during OTU clustering if gaps are not appropriately treated (Flynn et al 2015;THIS ISSUE). Considering the nature of rRNA genes (McTaggart and Crease, 2005;McTaggart and Crease 2009;Nyaku et al 2013), the issues raised here are likely to affect any study that applies these markers, regardless of the particular HTS technology employed. Given the conceptual and practical difficulty in translating OTUs to species, we argue that alternative approaches should also be considered when attempting to describe community composition.…”
Section: Discussionmentioning
confidence: 99%
“…Intra-individual variability of ribosomal cistrons is rare compared with the ITS but has been observed in some metazoans (Carranza et al 1996;McTaggart and Crease 2009), including nematodes (Bik et al 2013;Nyaku et al 2013). In the flatworm Dugesia mediterranea, two variants of the SSU region were found coexisting in the same individual.…”
Section: Number Of Nematodes Bmentioning
confidence: 99%
“…the SSU region were identified (Nyaku et al 2013), and these authors considered this as a result of a recombination event during unequal crossing over between sister chromatids or rDNA between the chromosomes X and Y, carrying coevolution of these sequences in these chromosomes. Thus, the presence of variant sequences with high affinity to A. fujianensis coexisting in specimens of A. besseyi could be evidence of a recent hybridization event, or even that these sibling species recently diverged from a common parental lineage.…”
Section: Number Of Nematodes Bmentioning
confidence: 99%